Development of Mathematical Model to Determining the Quantity of Required Alum (Al2(SO4)3.14H2O) at the Regional Water Utility Company in Pontianak (PDAM Tirta Khatulistiwa) - Wahyu Febri Ramadhy (Journal of Science and Science Education, 2020)
Water in Kapuas River is the raw material for clean water used by the regional water utility company in Pontianak or PDAM Tirta Khatulistiwa. Its quality was assessed through the main parameter called turbidity. To meet the clean water standard, the raw water must be undergoing a clean water treatment named coagulation using Aluminum Sulfate or Alum (Al2(SO4)3.14H2O) as coagulants. This alum must be determined its dosage to maintain the quality of the water itself. The company was using the jar-test method in order to determine the optimum dosage of alum due to its cheap price and ease. However, this method is inefficient in terms of time and cost for the laboratory. Therefore, we proposed the mathematical models which cheaper and efficient. This model build-up based on the data relationship between the optimum dosage of alum and turbidity in the coagulation process which obtained a mathematical equation that is . The offered mathematical model has resulted in turbidity values ​​that were following the Ministry of Health Regulation in 2010.